PENGARUH KUALITAS MAKANAN, PELAYANAN, HARGA DAN SUASANA RESTORAN TERHADAP KEPUTUSAN PEMBELIAN - Setyaningsih Sri Utami, Dita Wahyu Candra Sari, Sumaryanto & (Universitas Slamet Riyadi, 2017)
The purpose of this study was to know the effect of quality of food, service, priceand store atmosphere on consumer purchasing decisions This study is a survey. The typeof data used quantitative and qualitative data. The data source used primary datasources and secondary data. The study population is consumer Vien's Selat Segar danSop Solo. The research sample of 100 people with accidental sampling technique. Datacollection technique used questionnaire, observation and literature. Data were analyzedused multiple linear regression, t-test, F and coefficient of determination. The resultsshowed that the quality of food significantly effect on purchasing decisions. Services hassignificantly effect on purchasing decisions. Price has significantly effect on purchasingdecisions. Store atmosphere does not significantly effect on purchasing decisions. Thecoefficient of determination of 0,811 means that the contribution of variables influencethe quality of food, service, price and store atmosphere on purchasing decisions was81,1%, while the remaining 18,9% is influenced by other variables not studied, forexample, is location.Keywords: quaity of food, service, price, store atmosphere, purchasing decision